Electronic case log (Linux) - Reid, Peter; Reid, Helen (The University of Hull)
An electronic log book to organize and record findings in a scientific investigation or case study, with linked sections on locations, people, items, tests etc. Detailed guidance on use of the log is provided via a Help button at the top right corner of each section.